Aplikasi Sistem Pakar Pendeteksi Kerusakan Pada Mesin Bubut Menggunakan Metode Forward Chaining - Sri Harjanto; Gilang Pandhu Sudibya; Adriani Kusumaningrum (Journal of Information Technology, Computer Engineering and Artificial Intelligence (ITCEA), 2026)
A lathe machine is a tool capable of cutting metal into specific shapes, qualities, and dimensions as planned. Damage to a lathe machine is often difficult to identify and requires specialized handling; it typically needs to be transported to a workshop, which is both time-consuming and labor-intensive. Therefore, it is necessary to develop an expert system using the Forward Chaining algorithm to diagnose malfunctions in lathe machines. Forward Chaining is an inference method that initiates tracking by tracing data based on the facts of the observed symptoms. These symptoms are compared against standard rules and processed to generate solutions for the identified issues. The expert system is designed as a web-based application using the PHP programming language and a MySQL database. This system is intended to assist lathe machine operators and novice mechanics in identifying and addressing damages based on observed symptoms. Validation testing of this web-based expert system yielded a result of 83.3%, demonstrating its effectiveness in assisting users.